2011
DOI: 10.1002/adfm.201002278
|View full text |Cite
|
Sign up to set email alerts
|

Degradable Conjugated Polymers: Synthesis and Applications in Enrichment of Semiconducting Single‐Walled Carbon Nanotubes

Abstract: Polymers which enrich semiconducting single‐walled carbon nanotubes (SWNTs) and are also removable after enrichment are highly desirable for achieving high‐performance field‐effect transistors (FETs). We have designed and synthesized a new class of alternating copolymers containing main‐chain fluorene and hydrofluoric acid (HF) degradable disilane for sorting and preferentially suspending semiconducting nanotube species. The results of optical absorbance, photoluminescence emission, and resonant Raman scatteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 46 publications
(77 reference statements)
1
62
0
Order By: Relevance
“…The Raman spectra provided proof of the separation of the met-and sem-SWNTs [50][51][52] . For the HiPco-produced SWNTs, based on the Kataura plot 53,54 , we can estimate the ratio of the sem-or met-SWNTs using the RBM region in the Raman spectra measured by excitation at 633 nm, which is a widely used method 31,36,43,55 . Compared with the spectrum of the as-produced SWNTs (black line in Fig.…”
Section: Synthesis Of Cp-mmentioning
confidence: 99%
See 1 more Smart Citation
“…The Raman spectra provided proof of the separation of the met-and sem-SWNTs [50][51][52] . For the HiPco-produced SWNTs, based on the Kataura plot 53,54 , we can estimate the ratio of the sem-or met-SWNTs using the RBM region in the Raman spectra measured by excitation at 633 nm, which is a widely used method 31,36,43,55 . Compared with the spectrum of the as-produced SWNTs (black line in Fig.…”
Section: Synthesis Of Cp-mmentioning
confidence: 99%
“…1). Mayer and coworkers 42 and Chan-Park and coworkers 43 reported the use of degradable PFOalternating copolymers, with a photocleavable or acid-sensitive moiety, to irreversibly cleave the wrapping polymers in order to remove them from the composites. Although they could obtain the sem-SWNTs as bundles, the purity of the sem-SWNTs was rather low and complete removal of the wrapping polymer was not discussed.…”
mentioning
confidence: 99%
“…Besides, our group has researched the enrichment of s-SWNTs by degradable polyfluorene derivatives as well. [26] Based on the above researches, we found a promising separation method to obtain high purity of s-SWNTs by using water-soluble polyfluorene assisted agarose gel electrophoresis. There are two main factors for this effective method.…”
Section: Introductionmentioning
confidence: 99%
“…The di®erent colors represent the on-o® ratio of each device. Compared with pristine HiPco, which has a very low on-o® ratio (in the range of 1 to 10) as measured in our previous study, 43 the devices, prepared as described above from sorted SWCNTs, exhibit high values of on-o® ratio and e®ective mobility. Moreover, it was found that very sparsē lms (1 to 4 SWCNT m À2 ) do not form su±ciently conductive paths to yield measurable on-state current.…”
Section: Swcnt-based Fetsmentioning
confidence: 99%
“…In our previous research, 43 we had found that the residual impurity on the surface of sorted SWCNTs increases tube/tube contacts but reduces carrier mobility, thus limiting the maximum current and lowering the on-o® ratio. This problem can be eliminated by cleaning the surface of SWCNTs.…”
Section: Swcnt-based Fetsmentioning
confidence: 99%